Community structure analysis of endoparasitic helminths of Anabas testudineus (Bloch, 1792) from a fresh water body of Bangladesh - Bhuiyan, Aminul Islam; Ghani, Md Osman; Bushra, Jannatul (Journal of the Asiatic Society of Bangladesh, Science, 2014)
Community structure of the parasites of Anabas testudineus was analyzed collected from a fresh water body, Turag River at Diabari, Mirpur point of Dhaka, Bangladesh. Out of 50 A. testudineus fish observed, 36 (72%) were parasitized by at least one species of helminth endoparasites. Six metazoan endoparasites were recorded: two trematodes (Allocreadium minutum, Neopecoelina saharanpuriensis) and four nematodes (Ascaridida sp., Gnathostoma spinigerum, Contracaecum sp., Paragendria wallagonia). Prevalence was higher in female (81.25%) hosts than male (55.56%). Nematode was more prevalent group (70%) than trematode (62%). All parasite species were accounted as secondary species category; no central or satellite species accounted in the sample. A significant positive correlation was observed between the standard length of the host with the prevalence and abundance of all parasites in this sample fishes. Two parasites (A. minutum and Ascaridida sp.) showed typical over-dispersed distribution pattern and other four parasites (N. saharanpuriensis, G. spinigerum, Contracaecum sp. and P. wallagonia) showed random distribution pattern. Interspecies association between two species of parasite was moderately strong. The hosts sex did not affect the parasite diversity and abundance. J. Asiat. Soc. Bangladesh, Sci. 40(1): 67-77, June 2014